Non-Muslim Communal Divisions and Identities in the Early Modern Ottoman Balkans and the Millet System Theory - Kursar, Vjeran (Array, 2013)
According to a traditional and still widely accepted opinion, non-Muslims of various denominations in the Ottoman Empire were organized into separate units, so-called millets, based on a common religious creed. In front of the authorities millets were represented by their religious leaders, who were, following the logic of the Islamic law, and due to the lack of qualified laymen, in charge of administrative, executive and judicial affairs in their communities. However, there are a couple of points that bring into question postulates of the millet system theory. Apart from the questionable overvaluation of the authority and role of religious leaders and autonomy of the millets, critics disputed even the term millet itself and its use in the period before the Tanzimat reforms of the 19th century. Terms regularly used to designate non-Muslim groups and communities were tâ'ife, cemâ'at, kefere and dîn. The use of the term millet before the 19th century is very rare and almost exceptional. Sporadic occurrences of the term millet do not prove the existence of an administrative and political system named after it. The term millet originally means “confession, ” or “religion, ” and in that respect is equivalent of the term dîn. This is the meaning in which millet occurs in most of the cases. On the other hand, apart from the classical confessional designations such as “Christian, ” “Jew” or “non-believer, ” official Ottoman documents contain terms with specifically ethnic meanings, from common Rum for Orthodox Christians in general and Ermenî for the members of Armenian Church to more specific Sırf (“Serb”), Çingene (“Roma, ” “Gypsy”), Boşnak (“Bosnian”), Bulgar (“Bulgarian”), Macar (“Hungarian”), etc., which indicates that a certain level of ethnic and communal division or distinction may have existed. However, empire-wide organization of non-Muslim communities into three millets – Orthodox Christian, Armenian, and Jewish, while according to some authors the remaining Christian denominations and sects were included into two Christian millets, has no confirmation in the sources. A potential exception to the rule might be the Orthodox Christian millet within which the Patriarchate of Constantinople was acting as a unique religious organization of Orthodox Christians of the Empire until 1557 and the foundation of the Patriarchate of Peć. Members of other confessions were not organized into millets, although the term itself occurs from time to time, but were divided into numerous micro-communities determined by geographic, administrative, ethnic, cultural, economic and other factors.